There is an easier way

Geometry Level 3

( x 1 x 2 ) 2 + ( 2 x 1 2 9 x 2 ) 2 (x_1 - x_2)^2 + \left ( \sqrt{2-x_1 ^2} - \frac {9}{x_2} \right )^2

What is the minimum value of the above expression where x 1 ( 0 , 2 ) x_1 \in (0, \sqrt{2}) and x 2 R + x_2 \in R^+


The answer is 8.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Deepanshu Gupta
Mar 6, 2015

Observe that the formula is very similar to the distance formula, where the distance between ( x 1 , y 1 ) (x_1, y_1) and ( x 2 , y 2 ) (x_2, y_2) is equal to ( x 1 x 2 ) 2 + ( y 1 y 2 ) 2 \sqrt{ (x_1 - x_2) ^ 2 + ( y_1 - y_2) ^ 2 } .

If we consider the functions:
f ( x ) = 2 x 2 f : x 2 + y 2 = 2 g ( x ) = 9 x g : y = 9 x , \displaystyle{f\left( x \right) =\sqrt { 2-{ x }^{ 2 } } \Rightarrow f:\quad { x }^{ 2 }+{ y }^{ 2 }=2\\ g\left( x \right) =\cfrac { 9 }{ x } \Rightarrow g:\quad y=\cfrac { 9 }{ x } }, and consider the points ( x 1 , f ( x 1 ) ) (x_1, f(x_1) ) and ( x 2 , g ( x 2 ) ) (x_2, g(x_2) ) , we see that our task is to minimize the distance between these two curves (and then square the value).

We know that the minimum distance between 2 continuous, differentiable curves must satisfy the condition that the line joining both their points of contact must be normal to both curves. With some work, we can show that this must be y = x y = x .

Solving, we get the points ( x 1 , y 1 ) = ( 1 , 1 ) (x_1, y_1) = (1,1) and ( x 2 , y 2 ) = ( 3 , 3 ) (x_2, y_2 ) = (3, 3 ) .
Hence, the answer is equal to ( 3 1 ) 2 + ( 3 1 ) 2 = 8 (3-1)^2 + (3-1)^2 = 8 .

Ah .....Symmetry Kills this question . I shamelessly going through all calculation of normal equation . But Really +1 for your approach. :)

Karan Shekhawat - 6 years, 3 months ago

This is an awesome question! I too used symmetry to get answer within 30s!

Raghav Vaidyanathan - 6 years, 3 months ago

Done it the same way!

rishabh singhal - 5 years, 8 months ago
Deepak Sonawane
Apr 22, 2017

By partial differentiation with respect to X1 we get. 2 (X1 - X2) = [ (rt(2 - X1^2)) - 9 / X2 ] 1 / (rt (2 - X1^2)) * X1 by partial differentiation with respect to X2 (X2 - X1) = [ 9 / X2 - (rt(2 - X1^2/00] * 9 / X2

equating both the equations, we get X1 * X2^2 / rt ( rt ( 2 - X1^2)) = +- 3

as X2 should be +ve real no, so X2 = 3 and X1 = 1

substitute X2 = 3 and X1 = 1 in given expression

=(-2)^2 + (1 - 3)^2

= 8

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...